Penerapan Metode Apriori Pada Transaksi Penjualan Spare Parts Mobil - Maryam Hasan; Sudirman S Panna; Siska Udilawati; Almer Hassan Ali (Journal Of Informatics And Busisnes, 2025)
Until now, commercial vehicle manufacturers continue to innovate their products. One of the manufacturers is PT Nenggapratama Prima Nusantara, engaged in trade and services, namely HINO brand vehicles, spare parts, and services in direct collaboration with PT. Hino Motors Indonesia. The high demand and various types of spare parts certainly drive PT. Nenggapratama Prima Nusantara to maximize existing stock. It aims to ensure that there is no accumulation or shortage of goods. It is important to know the purchasing behavior of customers about which spare parts they buy together. One of the data processing methods usable for this problem is data mining with association analysis using Apriori algorithm. It is a data mining technique that produces rules to determine consumer habits in buying goods simultaneously at once. Based on the results of research using the Apriori method, the largest value (Support x Confidence) is obtained at 0.33. The biggest possibility is that if you buy the Dutro E-4 Fuel Strainer Kit, you will also buy Element Sub Assy Oil with a value of 0.33. Therefore, it can be seen that related spare parts can be arranged simultaneously.